1982
DOI: 10.2337/diacare.31.11.1023
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced Thermogenesis in Nondiabetic and Diabetic Obese Subjects

Abstract: The glucose-induced thermogenesis (GIT) following a 100-g oral glucose load has been measured by continuous indirect calorimetry in 55 nondiabetic and diabetic obese subjects of various ages and compared with two control groups of 17 young and 13 elderly nonobese subjects. The obese subjects were divided into four groups: group A, normal glucose tolerance; group B, impaired glucose tolerance; group C, diabetes with increased insulin response; group D, diabetes with reduced insulin response. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
2
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(66 citation statements)
references
References 0 publications
6
57
2
1
Order By: Relevance
“…However, the tendency for the energy expenditure to decrease in the subjects of group Illa (-0.114±0.063 kJ/min) during the insulin infusion was reversed after weight loss (+0.135±0.082 kJ/min) (P < 0.05). 10 of the 12 subjects showed a greater response after weight loss. In the five subjects of group Illa in whom the glucose infusion was started at least 35 min after beginning the insulin infusion, there was a decline (P < 0.05) in energy expenditure from 5.156±0.254 kJ/min during the base-line period to 4.970±0.215 kJ/min during the insulin infusion.…”
Section: Data Calculation and Analysismentioning
confidence: 89%
See 1 more Smart Citation
“…However, the tendency for the energy expenditure to decrease in the subjects of group Illa (-0.114±0.063 kJ/min) during the insulin infusion was reversed after weight loss (+0.135±0.082 kJ/min) (P < 0.05). 10 of the 12 subjects showed a greater response after weight loss. In the five subjects of group Illa in whom the glucose infusion was started at least 35 min after beginning the insulin infusion, there was a decline (P < 0.05) in energy expenditure from 5.156±0.254 kJ/min during the base-line period to 4.970±0.215 kJ/min during the insulin infusion.…”
Section: Data Calculation and Analysismentioning
confidence: 89%
“…Recently, a reduced thermic effect of a meal in obese subjects, in comparison with that of normal weight subjects, has been reported, (6)(7)(8)(9)(10). It has been postulated that this decreased dietary-induced thermogenesis might be involved in the etiology of obesity or the maintenance of the obese state.…”
Section: Introductionmentioning
confidence: 99%
“…Because a negative correlation between TEF and percent body fat has been reported, it can be suggested that this negative relationship exists independent of insulin resistance. Golay et al (36) examined TEF in relation to the degree of glucose intolerance. TEF was -10% in young individuals of normal weight and decreased with age and glucose intolerance, i.e., insulin resistance.…”
Section: Insulin Resistancementioning
confidence: 99%
“…21 It has been reported that obese patients having a long history of overweight as well as patients at the onset of obesity exhibit a decreased glucose-induced thermogenesis. 11,13,14 The factors involved in this defect are still under debate. On the one hand, a defective sympathetic response to food intake has been reported in Pima Indians who exhibit a high prevalence of obesity.…”
Section: Discussionmentioning
confidence: 99%